2008
DOI: 10.1093/pcp/pcn183
|View full text |Cite
|
Sign up to set email alerts
|

Widely Targeted Metabolomics Based on Large-Scale MS/MS Data for Elucidating Metabolite Accumulation Patterns in Plants

Abstract: Metabolomics is an ‘omics’ approach that aims to analyze all metabolites in a biological sample comprehensively. The detailed metabolite profiling of thousands of plant samples has great potential for directly elucidating plant metabolic processes. However, both a comprehensive analysis and a high throughput are difficult to achieve at the same time due to the wide diversity of metabolites in plants. Here, we have established a novel and practical metabolomics methodology for quantifying hundreds of targeted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
195
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(200 citation statements)
references
References 46 publications
4
195
0
1
Order By: Relevance
“…After harvesting, the cells were freeze-dried in a vacuum freeze dryer (FZ-2.5; Labconco) and then subjected to wide-target metabolome analysis by the methods described by Sawada et al (2009) with minor modifications. The freeze-dried BY-2 cell samples were crushed with a bead shaker (1,000 rpm, 2 min; ShakeMaster Neo; BMS), and 4 6 0.2 mg of sample was extracted with 80% (v/v) methanol by crushing with 5-mm zirconia beads (1,000 rpm for 2 min).…”
Section: Wide-target Metabolome Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…After harvesting, the cells were freeze-dried in a vacuum freeze dryer (FZ-2.5; Labconco) and then subjected to wide-target metabolome analysis by the methods described by Sawada et al (2009) with minor modifications. The freeze-dried BY-2 cell samples were crushed with a bead shaker (1,000 rpm, 2 min; ShakeMaster Neo; BMS), and 4 6 0.2 mg of sample was extracted with 80% (v/v) methanol by crushing with 5-mm zirconia beads (1,000 rpm for 2 min).…”
Section: Wide-target Metabolome Analysismentioning
confidence: 99%
“…Induced BY-2 cells were subjected to liquid chromatography-mass spectrometry (LC-MS)-based wide-target metabolome analysis as established by Sawada et al (2009), which can automatically detect approximately 700 metabolites that are the products of metabolic regulatory pathways (Sawada et al, 2009). This method can provide data on general metabolites during protoxylem vessel element formation with high reproducibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The newly developed methods of screening for potential alterations in the metabolism of the modified organism include the analysis of gene expression (microarrays, mRNA finger printing), overall protein analysis (proteomics), and secondary metabolites (HT-UHPLS-TOF-MS, MRM-TQMS; Grata et al 2009;Sawada et al 2009;Allwood and Goodacre 2010) that should be integrated into the risk assessment process. To sum up, the advances made in molecular biology, toxicology, biochemistry, and nutrition hold the promise of providing sets of genes and methodologies that serve as biomarkers for a cell's responses to toxins, allergens, or other compounds, which hold potential to the development of new tools to assess the GM crops.…”
Section: Nutritionally Enhanced Genetically Modified Crops and Biomentioning
confidence: 99%
“…37) Sawada et al reported widely targeted metabolome analysis using liquid chromatographtriple quadrupole-mass spectrometers (TQ-MS) by developing selected ion monitoring series of 378 metabolites. 38) Similar approaches are employed for the comprehensive analysis of lipids using liquid chromatograph-TQ-MS (lipidomics) 39) and analysis of primary metabolites using gas chromatograph-TQ-MS. 40) Although the number of measurable metabolites depends on the samples of interests, it has been reported that approximately 100-200 metabolites were usually analyzed by the widely targeted analysis. e widely targeted approach is now a productive and realistic strategy in metabolomics because the analysis could be performed using the more popular TQ-MS and default peak picking so ware developed by manufacturers.…”
Section: New Approach In the Metabolomics: Widely Targeted Analysismentioning
confidence: 99%